Cost-effectiveness Analysis of Peripherally Inserted Central Catheters Versus Central Venous Catheters for in-Hospital Parenteral Nutrition. Issue 7 (19th May 2022) - Comas, Mercè; Domingo, Laia; Jansana, Anna; Lafuente, Elisabeth; Civit, Anna; García-Pérez, Lídia; Lasso de la Vega, Carmen; Cots, Francesc; Sala, Maria; Castells, Xavier
Abstract : Objective: Our objective was to evaluate the cost-effectiveness of the use of peripherally inserted central venous catheters (PICCs) by a vascular access team (VAT) versus central venous catheters (CVCs) for in-hospital total parenteral nutrition (TPN). Methods: The study used a cost-effectiveness analysis based on observational data retrospectively obtained from electronic medical records from 2018 to 2019 in a teaching hospital. We included all interventional procedures requiring PICCs or CVCs with the indication of TPN. We recorded the costs of insertion, maintenance, removal, and complications. The main outcome measure was the incidence rate of catheter-associated bacteremia per 1000 catheter days. Cost-effectiveness analysis was performed from the hospital perspective within the context of the publicly funded Spanish health system. Confidence intervals for costs and effectiveness differences were calculated using bootstrap methods. Results: We analyzed 233 CVCs and 292 PICCs from patients receiving TPN. Average duration was longer for PICC (13 versus 9.4 days, P < 0.001). The main reason for complications in both groups was suspected infection (9.77% CVC versus 5.18% PICC). Complication rates due to bacteremia were 2.44% for CVC and 1.15% for PICC. The difference in the incidence of bacteremia per 1000 catheter days was 1.29 (95% confidence interval, −0.89 to 3.90). Overall, costs were lower for PICCs than for CVCs: the difference in mean overall costs was −€559.9 (95% confidence interval, −€919.9 to −€225.4). Uncertainty analysis showed 86.37% of results with lower costs and higher effectiveness for PICC versus CVC. Conclusions: Placement of PICC by VAT compared with CVC for TPN reduces costs and may decrease the rate of bacteremia.